2021
DOI: 10.1093/europace/euab155
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed field ablation prevents chronic atrial fibrotic changes and restrictive mechanics after catheter ablation for atrial fibrillation

Abstract: Aims Pulsed field ablation (PFA), a non-thermal ablative modality, may show different effects on the myocardial tissue compared to thermal ablation. Thus, this study aimed to compare the left atrial (LA) structural and mechanical characteristics after PFA vs. thermal ablation. Methods and results Cardiac magnetic resonance was performed pre-ablation, acutely (<3 h), and 3 months post-ablation in 41 patients with paroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 21 publications
4
80
0
Order By: Relevance
“…PEF ablation has brought about a change in the ablation catheter and ablation concept and is expected to be a new source of energy for arrhythmia ablation therapy, and the current findings suggest that this is a highly promising direction for clinical application ( 8 ). PEF ablation creates a larger and more homogeneous range of acute injury, which is beneficial in preventing decreased atrial/ventricular muscle compliance and in preserving atrial reserve and ejection function ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…PEF ablation has brought about a change in the ablation catheter and ablation concept and is expected to be a new source of energy for arrhythmia ablation therapy, and the current findings suggest that this is a highly promising direction for clinical application ( 8 ). PEF ablation creates a larger and more homogeneous range of acute injury, which is beneficial in preventing decreased atrial/ventricular muscle compliance and in preserving atrial reserve and ejection function ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nakatani et al recently showed that, compared to thermal ablation (radiofrequency or cryoablation), pulsed field ablation was associated with similar decreases in LA reservoir and booster pump functions and larger late gadolinium enhancement volume at cardiac magnetic resonance in the acute phase (<3 hours after ablation), while recovery of LA mechanical function and disappearance of the majority of late gadolinium enhancement in the chronic stage (3 months after ablation) was observed. [ 82 ] Of note, both alterations persisted in the chronic stage following thermal ablation. These findings suggest that tissue repair following pulsed field ablation involves less chronic fibrosis compared to thermal ablation, therefore resulting in better preservation of LA mechanical function.…”
Section: Catheter Ablation Of Af In Hfpefmentioning
confidence: 99%
“…Moreover, since cardiomyocytes have low sensitivity to PFA, a minimal risk of collateral damage is present. As shown in a recent imaging study, PFA results in an increased late gadolinium enhancement without injuring the microvasculature or inducing intramural hemorrhage, whereas the chronic fibrotic changes are of a lesser magnitude compared to thermal ablation techniques [ 89 ]. Additionally, the lack of coagulative necrosis with PFA suggests a minimal risk of incident pulmonary vein stenosis, as demonstrated by Kuroki et al [ 90 ].…”
Section: Atrial Fibrillation Catheter Ablationmentioning
confidence: 99%